Pengaruh Fasilitas Belajar Dan Disiplin Belajar Terhadap Hasil Belajar Kewirausahaan Siswa Program Keahlian Pemasaran Di SMK PGRI 3 Depok - Wahyu Adia Widia Sari; Fanni Erda Tasia (Pekobis : Jurnal Pendidikan, Ekonomi, dan Bisnis, 2021)
This study has the following objectives: 1) In order to know whether or not there is a significant influence between learning facilities on student entrepreneurship learning outcomes at SMK PGRI 3 Depok. 2) In order to know whether or not there is a significant influence between learning disciplines on student entrepreneurship learning outcomes at SMK PGRI 3 Depok. 3) In order to know whether or not there is a significant influence between learning facilities and learning discipline on student entrepreneurship learning outcomes at SMK PGRI 3 Depok.The research methodology used is a quantitative methodology. The population in this study were all students at SMK PGRI 3 Depok majoring in marketing with a total of 111 students. The sampling technique used is probability sampling, namely simple random sampling and obtained the number of 87 students. The research data was obtained using several methods, namely the first by using a questionnaire, the second using interviews and the third using documentation. The data that has been obtained is then analyzed using two methods, namely ''simple linear regression'' and ''multiple linear regression''.The results of this study indicate that: 1) There is a significant effect of the learning facilities variable on learning outcomes and the probability value is 0.000 <0.05. 2) There is a significant effect of learning discipline variables on learning outcomes and the probability value is 0.000 <0.05. 3) There is a significant effect of learning facilities and learning discipline variables simultaneously on learning outcomes and the probability value is 0.000 < 0.05 with the regression equation: Y = 8.501 + 0.478X1 + 0.349X2. From the determination test, it was found that R2 was 0.522, which means that the large contribution / contribution of the influence of learning facilities and learning discipline to learning outcomes is 52.2%.